Desenvolvimento de um dispositivo para reabilitação do punho humano - Brito, Lorena Souza Furtado (2019)
People affected by stroke may have spasticity causing difficulty in performing movements that compromise in daily living activities. The earlier, more intensive and repetitive the rehabilitation, better the results, but there is the difficulty of motivation and patient involvement. The use of robotic devices can aid in the rehabilitation process, providing improvements in motor and functional performance. The objective of this work is the development of a device to aid in this process. This device is directed to wrist rehabilitation movements, which is a joint that has 3 degrees of freedom to perform flexion/extension movements, adduction/abduction, and pronation/supination. The developed robotic structure has a base for hand support and is coupled to a servemotor. For the use of this mechanism, a serious game was developed as a graphical interface in which it consisted of hitting colored balls in each corresponding basket. In addition, with the structure control system, an impedance control was implemented, allowing the patient the intention of resisting the movement performed by the platform or assisting it with the required movement. Fourteen healthy participants performed the exercises with the device and subsequently responded to an Intrinsic Motivation Inventory (IMI), which resulted in a high degree of approval, competence and relaxation during the performance of the proposed activities. Three volunteers post stroke participated in the study. They performed, for a month, in 4 sessions of 15 minutes of robotic therapy. After the tests were performed, improvements and amplitude gain were observed for the wrist flexion and extension movements of all patients. In this way, the proposed device could be a tool to assist health professionals in the procedures and processes of rehabilitation.